Are overqualified employees bad apples? A dual-pathway model of cyberloafing. Issue 1 (14th August 2019) - Zhang, Junwei; Akhtar, Muhammad Naseer; Zhang, Yajun; Sun, Shan
Abstract : Purpose: Drawing from cognitive and emotional perspectives, the purpose of this paper is to theorize and test a dual-pathway model in which moral disengagement and anger toward organization act as two explanatory mechanisms of the association between perceived overqualification and employee cyberloafing. The authors further proposed that the strengths of these two mediating mechanisms depend on employee moral identity. Design/methodology/approach: The authors used hierarchical linear modeling to examine the hypotheses by analyzing a sample of 294 employees working in 71 departments in China. Findings: Results revealed that moral disengagement and anger toward organization mediated the positive link between perceived overqualification and cyberloafing beyond the influence of social exchange. Furthermore, moral identity attenuated the association between the mediators (i.e. moral disengagement and anger) and cyberloafing and the indirect relationship between perceived overqualification and cyberloafing. Originality/value: Extant studies have examined the effects of perceived overqualification on employee behaviors in terms of task performance, organizational citizenship behavior, proactive behavior, as well as withdrawal behavior. The study expands this line of research by empirically investigating whether and how perceived overqualification influences cyberloafing.